2020
DOI: 10.1177/1087054720956714
|View full text |Cite
|
Sign up to set email alerts
|

Context Regulation of Mind Wandering in ADHD

Abstract: Objective We aimed to understand the association between MW frequency and clinical measures, context regulation of MW and group differences in task performance. Method 27 adults with ADHD and 29 controls performed tasks manipulating demand on working memory and sustained attention, and recorded their MW frequency using probes. Results A significant association between MW frequency and the clinical measures was demonstrated. Along with increased MW frequency, individuals with ADHD reported decreasing MW frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
(100 reference statements)
5
15
0
Order By: Relevance
“…With regards to our previous ERP findings, we found that individuals with ADHD showed significantly reduced P1 amplitudes (reflecting early sensory processes) relative to controls during periods of task focus, but no differences during MW episodes. Conversely, P3 amplitudes (reflecting attention allocation) were lower in those with ADHD than controls during MW but not during task focus ( Bozhilova et al, 2021a , Bozhilova et al, 2021b ). Given the strong association of MW with ADHD symptomatology and associated daily life difficulties ( Bozhilova et al, 2018 ), identifying the neural correlates of real-time MW levels may suggest new ways to monitor treatment effects in individuals with ADHD, with the potential to improve future treatment practices.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…With regards to our previous ERP findings, we found that individuals with ADHD showed significantly reduced P1 amplitudes (reflecting early sensory processes) relative to controls during periods of task focus, but no differences during MW episodes. Conversely, P3 amplitudes (reflecting attention allocation) were lower in those with ADHD than controls during MW but not during task focus ( Bozhilova et al, 2021a , Bozhilova et al, 2021b ). Given the strong association of MW with ADHD symptomatology and associated daily life difficulties ( Bozhilova et al, 2018 ), identifying the neural correlates of real-time MW levels may suggest new ways to monitor treatment effects in individuals with ADHD, with the potential to improve future treatment practices.…”
Section: Introductionmentioning
confidence: 79%
“…The testing session for all participants lasted approximately 3–4 h and included a clinical interview for ADHD (DIVA 2.0), IQ testing and self-report measures, and two computerised tasks with simultaneous EEG recordings preceded by a practice session for each task ( Bozhilova et al, 2021a , Bozhilova et al, 2021b ). Participants were asked not to smoke, consume caffeinated/alcoholic drinks, and take non-illicit substances on the day of the testing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations